Efecto de la terapia dialéctica conductual en los trastornos de conducta alimentaria - Borjas Molina, Stephanie Adriana (2024)
In recent years, eating disorders (EDs) have gained greater significance due to their increasing incidence and difficulty in treatment. The symptomatology of these disorders often cannot be effectively addressed, leading to a need for new treatment alternatives. Dialectical Behavior Therapy (DBT) has emerged as a promising option due to the results it brings. Therefore, the objective of this review is to determine the effect of DBT in the treatment of EDs, specifically anorexia nervosa, bulimia nervosa, and binge eating disorder. We searched the databases: Web of Science, EBSCOhost, Scopus, following PRISMA guidelines, resulting in the selection of ten scientific articles that met the eligibility criteria. It was found that DBT and its adaptations had significant results in reducing symptoms related to the reviewed EDs, and these improvements persisted over time even after discharge. It is concluded that DBT is a promising treatment in addressing the symptomatology of EDs. However, further research in the national context is relevant to generate results that improve intervention.